As causativas sintéticas no português do Brasil: novas evidências a favor da estrutura bipartida do VP - Yara Rosa Bruno da Silva (2009)
The central purpose of this research is to discuss the formation ofsynthetic causative sentences in Brazilian Portuguese (PB), mainly in Mineiro dialect, in order to bring evidences in favor of the bipartite structure of the VP. We aim at showing that the synthetic causative sentences are equivalent to complex predicates, composed of two heads: one causative v0 and one X0, the proposal is that the latter is the complement of v0. Synthetic causatives are evidence in favor of a more articulated structure of the VP. We also assume in this research the Hale and Keyser (1993; 2002) hypothesis, according to which a synthetic causative structure is generated by means of a syntactic operationcalled conflation. In this operation, the phonological matrix of an X0 head is transferred to the head of the vP projection. Additionally, we show thatunergative verbs constitute a special verb class, since they can appear incausatives sentences, projecting a bipartite structure with two heads: thecausative vo head and the lexical Vo head. This proposal clearly contradicts one of the Hale e Keysers predictions, according to which unergatives do not occur in causative structures. Its important to say that this research follows theoretical assumptions from the Generative Grammar Theory, particularly those assumed by Hale and Keyser (1993; 2002), and the semantic-syntax interface approaches such as those developed recently by Cançado (1995; 2003).